STATUS KUALITAS AIR WADUK CIRATA DAN DAMPAKNYA TERHADAP PERTUMBUHAN IKAN BUDIDAYA - Wage Komarawidjaja (Jurnal Teknologi Lingkungan, 2005)
Waduk Cirata is multipurpose cascade dam that lay in the middle of Citarumwatershed. Based on some reports, the water quality of this dam significantlydecreased to bad condition. This condition may be harmful to some equipmentsgenerating electricity power and also aquaculture product utilizing cages (KJA).The result of intensive observation during carps (Cyprinus carpio) culture periodconcluded that its aquaculture water changed into polluted called Eutrophicenvironment. There is correlation between eutrophication and lack growth of fishes in some cages. It is indicated by dominant increase of fish length than the increase of the weight of fish which is called as a negative allometric of fish growth.